Conservation and sustainable use of agricultural biodiversity : (CIP-UPWARD, 2003)
Three Volumes including, Understanding Agricultural diversity. Strengthening Local Mangagement of Agricultural Biodiversity. Ensuring an Enabling Environment for Agricultural Biodiversity. These sourcebooks include 75 articles.